PERTUMBUHAN DAN PERKEMBANGAN UMKM SHANAYA TEA - Dian G Purba; Rospita C.Y Siahaan; Agustama Wani; Silvia Paramitha Purba; Faisal Alviandi Siadari; Tommi H Damanik; Fahri I Siregar (CV. Denasya Smart Publisher, 2024)
This journal discusses the contribution of Shanaya Tea Micro, Small and Medium Enterprises (MSMEs) in developing the local tea industry. Through this research, we analyze marketing strategies, product innovation and the role of MSMEs in increasing consumer awareness about local tea. The results show that Shanaya Tea has succeeded in strengthening the image of local tea through promoting sustainable products and collaborating with local tea farmers. The implication of this research is the importance of government support and collaboration between MSMEs to strengthen the position of the local tea industry in the domestic market. This research also reveals the challenges faced by Shanaya Tea MSMEs, including in terms of financing, regulations and market penetration. Nevertheless, Shanaya Tea's success shows the great potential of MSMEs in supporting product diversification and local economic development. The practical implication of this research is the importance of developing policies that support MSMEs in non-leading industrial sectors such as the tea industry. Further research can explore more deeply the collaboration strategies between MSMEs as well as the social and economic impacts of the development of the local tea industry in Indonesia. Apart from that, this research also highlights the importance of a sustainable approach in developing MSMEs in the agro-industrial sector. The results provide valuable insights for practitioners, academics and policy makers in understanding the role of MSMEs in the national economy as well as the efforts needed to increase the competitiveness of the local tea industry. Further research can dig deeper into marketing strategies and supply chain management in the context of MSMEs in the agro-industrial sector.